Primary Cell Lines From Feathers and Blood of Free-Living Tawny Owls (Strix aluco): A New In Vitro Tool for Non-Lethal Toxicological Studies - Kroglund, Ingvild Buran; Eide, Sara Kristiane Kjærgård; Østnes, Jan Eivind; Kroglund, Rolf Terje; Frisli, Jan-Erik; Waugh, Courtney Alice (Frontiers in Genetics, 2022)
The validation of the use of primary cell lines from non-lethal matrixes of feathers and blood of nestlings of a wild bird species, the tawny owl (Strix aluco) is described. Tawny Owl Feather Fibroblast (TOFF) cells and peripheral blood mononuclear cells (PBMCs) were isolated and cultured from the pulp of the secondary wing feathers and whole blood respectively from free-living tawny owl nestlings. Cell growth was registered up until 48 hours for both the PBMC cells and the TOFFs. The validation of these primary cell lines in free-living birds has the potential to advance the assessment of immunotoxicological effects in wildlife via non-lethal manner. They provide a key tool with which to study cell toxicity and responses to environmental stressors on a cellular level in wild bird species of interest.